PENDAMPINGAN SISTEM INFORMASI AKUNTANSI DALAM PENGELOLAAN LAPORAN DI PEMERINTAH DESA PALASARI KECAMATAN UJUNG JAYA KABUPATEN SUMEDANG - firdaus, dony waluya (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2024)
The village government strives for accountable village financial management and the use of village financial information systems as village efforts in the transparency of village finances. Accountable and transparent village financial reports can increase the trust of the village community so that the village can be accountable for village finances. The implementation of WEB Desa with Community Service activities in Palasari Village, Ujung Jaya District, Sumedang Regency using survey, interview, and community service methods in Palasari Village is carried out online using zoom media.